Promoting youthfulness: the construction of persuasive discourse and argumentation - Tuna, Sandra (Redis: Revista de Estudos do Discurso, 2019)
Advertising discourse is persuasive by its very nature. Essentially goal-oriented, it is constructed so as to propose a pre-determined view of the world that suits its purposes, by means of a well-defined argumentative pathway that leads up to the proposed most (desired) suitable option. As a discourse that enjoys unparalleled freedom – both in terms of content and form – it has long moved beyond a clear-cut argumentative process based on hard sell versus soft sell, or tickle versus reason approaches (Cook, 2001:15). In their attempts to overcome boredom and scepticism on the part of an ad-literate audience, advertisers resort to different forms of argumentative reasoning: deduction, opposition, analogy or calculation, as proposed by Charaudeau (2008). In addition, as multi-modal texts, they make the most of the different modes available – pictures, text, sound, moving pictures – to build their argument. As claimed by Ripley (2008), an ad is an argument, thus, whichever claims or statements it makes, we are aware of – and suspicious about – its persuasive intent, though we often tend to go along with the worldviews it suggests. In spite of common accusations of stereotyping, segregating, imposing models of beauty, lifestyle among others, overlooking (and blurring) national idiosyncrasies, advertising has somehow managed to build rather convincing arguments that seemingly consider such criticism. In this study, we will look into cosmetics adverts that explicitly and implicitly build their arguments in ways that almost always encourage identical proposals of youthfulness, despite their apparent different claims and argumentative routes and despite their apparent concern for incorporating socially (or politically) correct positions.